Spectrum of Neurological cases in OPD of Tertiary Paediatric care Center of Nepal - Adhikari, Santosh; Prajapati Manandhar, Bina; Jha, Anshu; Bista, Tek Bahadur; Bhattarai, Srijana; Bichha, Muskan (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Advancement of different mortality of investigation and super specialization of medical science has been able to develop different diagnosis and treatment possible. Neurology is one of the super specialties. Cases are increasing day by day. We aimed to change the data of paeditric neuro OPD. Methods: Those cases that visited the Neuro department of only one governmental tertiary paediatric care center of Nepal and have been registered in outpatient register were analyzed. Mean, frequency etc. were calculated using Microsoft excel. Results: Out of diagnosed 2517 patients, 64.48% (N = 1623) were males, 35.51% (N = 894) were females. The mean age of the children was 57.64. Global developmental delay comprised 24.19% (N = 609), epilepsy comprised 21.81% (N = 549), motor delay comprised 5.68% (N = 143), intellectual delay comprised 1.98% (N = 50), speech delay comprised 3.33% (N = 84), febrile seizure comprised 3.41% (N = 86, 3.41%), seizure disorder comprised 16.84% (N = 424), headache / migraine comprised 3.33% (N = 84), Duchene muscular dystrophy and spinal muscular atrophy comprised 1.5% (N = 38), cerebral palsy comprised 2.41% (N = 61), acute encephalitis syndrome comprised 1.23% (N = 31) and others were 1.03% (N = 26) diagnosis made in the Neuro OPD. Conclusions: Our study showed that there were more male children in Neuro OPD than females and the commonest morbidities included global development delay, hypoxic ischemic encephalopathy, seizure disorder in children visiting the Neuro OPD in tertiary paediatric care center of Nepal.